2013
DOI: 10.1097/spv.0b013e318285bbed
|View full text |Cite
|
Sign up to set email alerts
|

Transvaginal Sling Release With Intraoperative Ultrasound Guidance

Abstract: Surgical transection of a tension-free vaginal tape can be safely performed under the guidance of ultrasound. At her 12-month follow-up visit, the patient did not have urinary incontinence or voiding dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Although ultrasound has been used intraoperatively in TVT, it has only been applied to post-surgical complications, mainly to excision or lysis of tapes, taking advantage of the ease of locating them with ultrasound. 20 Among the weaknesses of this study, we found that ultrasound is a technique that is very highly operator-dependent and with a long learning curve; in our case, all the tapes were placed by the same surgeon, who has extensive experience with ultrasound in TVT-O control. This could imply that our results cannot be extrapolated to surgeons without this expertise in ultrasound.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Although ultrasound has been used intraoperatively in TVT, it has only been applied to post-surgical complications, mainly to excision or lysis of tapes, taking advantage of the ease of locating them with ultrasound. 20 Among the weaknesses of this study, we found that ultrasound is a technique that is very highly operator-dependent and with a long learning curve; in our case, all the tapes were placed by the same surgeon, who has extensive experience with ultrasound in TVT-O control. This could imply that our results cannot be extrapolated to surgeons without this expertise in ultrasound.…”
Section: Discussionmentioning
confidence: 85%
“…Although ultrasound has been used intraoperatively in TVT, it has only been applied to post‐surgical complications, mainly to excision or lysis of tapes, taking advantage of the ease of locating them with ultrasound 20 …”
Section: Discussionmentioning
confidence: 99%